Challenges and Innovations in Teaching The Arabic Grammar to Non-Native Speakers - Salim, Dr. Mohammad Salim (Integrated Journal for Research in Arts and Humanities, 2024)
This study explores the challenges associated with teaching the Arabic grammar to non-native speakers and highlights educational and technological innovations aimed at improving teaching quality. The first chapter addresses the complexity of the Arabic morphological and syntactic system, the flexibility of syntactic order, and phonetic and orthographic challenges, alongside educational challenges such as curriculum design, teacher training, and assessment difficulties. The study aims to provide practical solutions to enhance the effectiveness of teaching the Arabic grammar through the development of flexible curricula, training teachers in modern methods, and adopting diverse assessment approaches. Additionally, the article discusses recent innovations in teaching the Arabic grammar, focusing on the role of technology and artificial intelligence in improving grammar instruction methods. It examines modern pedagogical approaches, such as task-based learning, communicative teaching, and the flipped classroom model, as well as integrated programs that enhance grammar learning through real-life and cultural contexts. Moreover, the role of edutainment in enhancing students' grammar learning experience and increasing engagement in an enjoyable and effective educational environment is also highlighted.